Proximal and Distal Minimally Invasive Plate Osteosynthesis of Four-Piece Tibial Fracture: Case Report - Gurger, Murat; Batur, Omer Cihan; Celik, Suat (Derman Medical Publ, 2013)
Although there are many treatment options in complex fractures and following injuries in simple fractures, treatment choices become narrow and there will be difficulties in determining the most appropriate method. We have presented our case which involves a four-piece-tibial fracture and lung injury that we treated with plated osteosynthesis that minimally invasive from proximal and distal.
Keywords: Osteosynthesis; Fracture; Minimally Invasive Surgical Procedures